Hubungan Pengetahuan Sikap dan Pendidikan Ibu terhadap Kepatuhan Ibu dalam Melakukan Kunjungan Antenatal Care (ANC) di Klinik Kasih Ibu Kota Jambi Tahun 2021 - Putri Agustina; Silvia Mariana (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
According to WHO estimates worldwide more than 500,000 mothers die each year during pregnancy or childbirth. This can be prevented through monitoring or antenatal care examinations. The aim of the study was to determine the relationship between knowledge, attitudes and education on the adherence of pregnant women in carrying out antenatal care visits. This research is an observational-analytical study with a cross-sectional approach carried out in two ways, namely univariate analysis and bivariate analysis. The research was conducted at the Kasih Ibu Pasir Putih Clinic, Jambi City in May 2021. The population in this study were all mothers who made antenatal care visits (ANC) as many as 33 people and a sample of 33 people. The results showed that there was a relationship between knowledge of attitudes and mother's education on mother's compliance in conducting antenatal care visits before and after health education was given to respondents' knowledge about the importance of antenatal care visits with a p-value of 0.000.